Pharmacologic side effects and/or neurologic disorder : case report - Radanović-Grgurić, Ljiljana (Array, 2009)
The authors presented a patient with schizophrenia and with early parallel development of neurologic symptoms. At first, symptoms were manifested by extrapyramidal syndrome due to appliance of typical neuroleptics. Therefore, therapeutic approach was diverted to implementation of atipycal antiypsychotics. Consequently patient developed orofacial diskyinesias which progrediated in unilateral choreo-atetoid movements. This followed two hospitalizations for diagnostic workup and correction of therapy. Only repeated brain MR showed moderate cortical atrophy. Still remains the question whether primary neurologic disorder provoked psychotic process or there were two separate disorders where pharmacologic intervention accelerated expansion of neurologic disorder.